Design and fabrication of an automatic ceiling fan cleaner / Muhammad Aniq Iqmal Aminudin - Aminudin, Muhammad Aniq Iqmal (2023)
The project design based on the finite element analysis for a new ceiling fan cleaner. Objectives of this projects are to design a new project that ergonomic for users such as safety and user-friendly. As we know, users commonly cleaning their fan using an old method. Using that method, it will make users will feel unsafety and cleanliness. Based on past research, this thesis focuses on the creation of a new design that can overcome all the difficulties experienced. The design was develop using solid works software to view three-dimensional model. A survey method was used on the local community members who were experiencing issues. Based on the findings of how to solve those issues, we know that the ideal technique is to use an adjustable rod, a roller with a motor and a waste box to collect dust. As a result, all users of our products will be able to save money and time